Standard Scores for Selected Mechanical Officiating Situations in Basketball Among Fourth-Year Female Students at the College of Physical Education and Sports Sciences, University of Baghdad - Noor Eldeen Ali Madhloom (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2026)
The study aimed to design officiating situations according to the three-person officiating mechanics system and present them to fourth-year female students. The research population consisted of (166) female students, of whom (62) were excluded due to absence or because they were active players. Thus, the final sample consisted of (99) female students. Three different models were presented for each officiating situation, distributed into three colors (blue, red, and black). The blue option represented the most correct officiating decision and was awarded (3) points, while the red option received (2) points, and the black option received (1) point. The researcher employed the descriptive method due to its suitability to nature of study. The results were obtained in form of raw scores, which represent original scores derived from application of tests or any other measurement tool before being statistically processed, difficulty lies in interpreting these scores, as their meaning and significance are not easily understood without further analysis.